Rapid decline in river icings detected in Arctic Alaska: Implications for a changing hydrologic cycle and river ecosystems - Tamlin M. Pavelsky; Jay P. Zarnetske (Geophysical Research Letters)
Abstract Arctic river icings are surface ice accumulations that can be >10 km2 in area and >10 m thick. They commonly impact the hydrology, geomorphology, and ecology of Arctic river environments. Previous examination of icing dynamics in Arctic Alaska found no substantial changes in extent through 2005. However, here we use daily time series of satellite imagery for 2000–2015 to demonstrate that the temporal persistence and minimum summertime extent of large icings in part of Arctic Alaska and Canada have declined rapidly. We identified 122 large ephemeral icings, and 70 are disappearing significantly earlier in the summer, with a mean trend of −1.6 ± 0.9 day−1 for fully ephemeral features. Additionally, 14 of 25 icings that usually persist through the summer have significantly smaller minimum extents (−2.6 ± 1.6% yr−1). These declines are remarkably rapid and suggest that Arctic hydroclimatic systems generating icings, and their associated ecosystems, are changing rapidly.